Financial well‐being of Malaysian college students - Sabri, Mohamad Fazli; Cook, Christine C.; Gudmunson, Clinton G. (Emerald Group Publishing, 2012)
Purpose: The purpose of this paper is to examine the relationships between personal and family backgrounds, academic ability, childhood consumer experience, financial socialization, financial literacy, and perceived financial well‐being of college students. Design/methodology/approach: Data were collected using a multi‐stage sampling technique from 11 public and private universities across Malaysia and the sample consists of 2,219 college students. Structural equation modelling was utilized to test the hypotheses. Findings: Childhood consumer experiences such as savings habits contribute to students’ financial well‐being (money saved, current financial situation, and financial management skills). Financial socialization agents, for example, through parents and religion sources could increase college students’ financial well‐being. Financial literacy was related to financial well‐being. There were important differences between the Malay and Chinese ethnic groups in Malaysia. Research limitations/implications: Overall, implications and recommendations for future research, teaching, and public policy are also provided for parents, college administrators, counselors and educators. Originality/value: This research provides meaningful information about how various factors (childhood experience, financial socialization, and financial literacy) predict students’ financial well‐being.